Functional Relationship Between T15 and J558 Idiotypes in BALB/c Mice - Vakil, Meenal (Hindawi Publishing Corporation, 1991)
In inbred strains of mice, antiphosphorylcholine (PC) and anti-α1,3 dextran (DEX). antibodies are structurally distinct from each other and have been shown to exhibit noncrossreactive antigen binding and idiotypic specificities. However, the prototype anti-PC and anti-DEX antibodies, TEPC15 and J558, respectively, were shown to be connected via a common autoantiidiotypic monoclonal antibody isolated from newborn BALB/c mice. The capacity of various monoclonal anti-PC and anti-DEX antibodies as well as the antigens PC and DEX to modulate T15 and J558 idiotypes in BALB/c mice was tested by their administration to newborn mice. Anti-PC antibodies of the .T15 idiotype injected into 2-4-day-old mice, at a time when T15 anti-PC precursors develop in BALB/c mice, suppressed the anti- PC response of these mice at 6 weeks of age. Similarly, J558 antibodies injected into 8-12-day-old mice, at a time when J558 precursors normally develop, suppressed the response to DEX. As a further demonstration of this connectivity, the injection of J558 into 4-day-old mice led to a down modulation of T15 idiotype, whereas both T15 and a minor idiotypeexpressing antibody M167 when injected into 8-12-day-old mice caused a reduction in expression of the J558 idiotype. As predicted from in vitro analysis, injection of anti-PC antibodies of the M167 idiotype 2 to 4 days after birth enhanced the subsequent response to PC. However, anti-PC antibodies expressing another minor M603 idiotype did not affect the PC. response. The results parallel the in vitro enhancement of M167 antibodies but not M603 on T15 binding to antiidiotype in vitro. Similarly, anti-DEX antibodies expressing the M104E idiotype had no detectable effects on the capacity to respond to PC or DEX or on the expression of T15 and J558 idiotypes as adults. Exposure of newborn mice to PC led to a dramatic reduction in the response to DEX as adults, whereas exposure to DEX at this stage of development had no effect on response to PC as adults. Collectively, these observations provide evidence for a complex functional connectivity between T15 and J558 idiotype-bearing B cells during ontogeny and extend our previous observations that development of these idiotypes is regulated by idiotype-directed interactions between B cells or their immunoglobulin products.